The respective hardening contributions of dislocations and twins to the flow stress of a twinning-induced plasticity steel. (February 2016) - Liang, Z.Y.; Li, Y.Z.; Huang, M.X.
Abstract: Deformation twins in twinning-induced plasticity (TWIP) steels have been considered in the literature as the source of back stress and kinematic hardening, which contribute considerably to the flow stress. Nevertheless, it is demonstrated in the present work that the contribution of twins to the flow stress is limited. Instead, dislocations, via forest hardening, account for up to ~ 90% of the flow stress increment after yielding in the present TWIP steel. In other words, dislocation evolution dominates the work-hardening rate of TWIP steels. Graphical abstract: